2022
DOI: 10.1038/s41598-022-16999-2
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus H7-protein is required for the organization of the viral scaffold protein into hexamers

Abstract: Viruses of the giant virus family are characterized by a structurally conserved scaffold-capsid protein that shapes the icosahedral virion. The vaccinia virus (VACV) scaffold protein D13, however, transiently shapes the newly assembled viral membrane in to a sphere and is absent from the mature brick-shaped virion. In infected cells D13, a 62 kDa polypeptide, forms trimers that arrange in hexamers and a honey-comb like lattice. Membrane association of the D13-lattice may be mediated by A17, an abundant 21 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, cryo-ET examinations of deletion mutants of viral membrane assembly proteins (VMAPs), a group of proteins including L2, A30.5, A11, A6 and H7, demonstrated that one or more VMAPs interact for ER membrane hijacking and the separation of viral membrane from its origin (Suarez et al 2017;Weisberg et al 2017). Recent study proposed H7 is directly relevant in hexameric organization of D13 scaffold protein, suggesting complex interactions among VMAPs, D13, A17 and A14 (Tonnemacher et al 2022).…”
Section: In the Era Of Cryo-3demmentioning
confidence: 99%
“…For example, cryo-ET examinations of deletion mutants of viral membrane assembly proteins (VMAPs), a group of proteins including L2, A30.5, A11, A6 and H7, demonstrated that one or more VMAPs interact for ER membrane hijacking and the separation of viral membrane from its origin (Suarez et al 2017;Weisberg et al 2017). Recent study proposed H7 is directly relevant in hexameric organization of D13 scaffold protein, suggesting complex interactions among VMAPs, D13, A17 and A14 (Tonnemacher et al 2022).…”
Section: In the Era Of Cryo-3demmentioning
confidence: 99%